2019
DOI: 10.1371/journal.pntd.0007464
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stress responses of Sodalis glossinidius, an indigenous bacterial symbiont of hematophagous tsetse flies

Abstract: Tsetse flies (Diptera: Glossinidae) house a taxonomically diverse microbiota that includes environmentally acquired bacteria, maternally transmitted symbiotic bacteria, and pathogenic African trypanosomes. Sodalis glossinidius, which is a facultative symbiont that resides intra and extracellularly within multiple tsetse tissues, has been implicated as a mediator of trypanosome infection establishment in the fly’s gut. Tsetse’s gut-associated population of Sodalis are subjected to marked temperature fluctuation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 83 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…Loss of diversity persists months after the heat stress itself ( 43 ) and is associated with decreased digestive efficiency ( 44 ). Furthermore, the bacterial symbionts of several insects collapse entirely under heat stress, with severe consequences for host vitality ( 21 23 , 45 ). Importantly, a heat shock gene variant in Buchnera , an obligate intracellular aphid symbiont, mediated the temperature sensitivity of the entire organism, including decreased fertility of the aphid during heat stress ( 23 ).…”
Section: Environmental Heat Stress and The Intestinal Microbiomementioning
confidence: 99%
“…Loss of diversity persists months after the heat stress itself ( 43 ) and is associated with decreased digestive efficiency ( 44 ). Furthermore, the bacterial symbionts of several insects collapse entirely under heat stress, with severe consequences for host vitality ( 21 23 , 45 ). Importantly, a heat shock gene variant in Buchnera , an obligate intracellular aphid symbiont, mediated the temperature sensitivity of the entire organism, including decreased fertility of the aphid during heat stress ( 23 ).…”
Section: Environmental Heat Stress and The Intestinal Microbiomementioning
confidence: 99%
“…Indeed, the identified bacteria belonged to genera that have been recognized to manipulate insect reproduction via male-killing and parthenogenesis ( Rickettsia and Flavobacterium ) [ 59 , 60 ], supply amino acids and vitamins to their hosts ( Enterobacter , Sodalis , Rhodococcus , and Pantoea ) [ 61 , 62 , 63 , 64 ], or provide insecticide resistance to their host ( Rickettsia and Citrobacter ) [ 65 , 66 ]. Some are also capable of fixing nitrogen within the insect host ( Enterobacter ) [ 37 ], producing antibiotics ( Streptomyces ) [ 67 ], and providing insect protection against parasitoids (e.g., Serratia and Providencia ) [ 68 , 69 ] or heat stress ( Serratia and Sodalis ) [ 70 , 71 ]. The Halomonas genus was also detected in our study, but although members have been recognized as insect symbionts [ 50 ], their specific role has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that heat tolerance, longevity and/or fecundity are reduced when these bacterial symbionts are pharmaceutically eliminated (Dale & Welburn, 2001 ; Pais et al., 2008 ). Moreover, Sodalis glossinidius does not grow at temperatures above 31°C and is unable to survive for more than 48 h at 30°C (Roma et al., 2019 ). These bacteria were likely killed in the 31°C treatments and may have influenced the ability of tsetse to respond adaptively.…”
Section: Discussionmentioning
confidence: 99%